2011
DOI: 10.1002/jcp.22729
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Allies or Foes in erythropoiesis?

Abstract: SUMMARY MicroRNAs are small non-coding RNAs that negatively regulate gene expression through mRNA degradation or translational repression. It is becoming increasingly recognized that miRNAs play central roles in almost all cellular processes, and especially during development. The function of miRNAs in hematopoiesis, including erythropoiesis, is beginning to be elucidated. In this review, we will focus on what is known about miRNA function in various aspects of erythropoiesis and red cell physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 67 publications
1
37
0
1
Order By: Relevance
“…There is growing evidence that miRNAs regulate hematopoiesis in both hematopoietic stem cells and committed progenitor cells [17][18][19][20][21][22][23][24][25]. Deregulated miRNA profiles have been reported in MPN patients during in vitro erythroid differentiation as well as in peripheral blood granulocytes, platelets, and reticulocytes [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that miRNAs regulate hematopoiesis in both hematopoietic stem cells and committed progenitor cells [17][18][19][20][21][22][23][24][25]. Deregulated miRNA profiles have been reported in MPN patients during in vitro erythroid differentiation as well as in peripheral blood granulocytes, platelets, and reticulocytes [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In mice lacking Ago2 Gene, defective B cells and erythroid maturation as well as increased basophilic erythroblasts together with significant reduction in mature orthochromatic erythroblasts is observed (Cheloufi et al, 2010). It is not clear how the reduction or absence of Ago2 impairs erythropoiesis, and its impact on expression of miRNAs is a suggested mechanism because the lack of Ago2 protein reduces the expression level of miRNAs, including miR-451 (O'Carroll et al, 2007;Byon and Papayannopoulou, 2012). It has also been shown that the expression level of miRNA-376a is high in early precursor cells and is reduced during cell differentiation.…”
Section: Role Of Mirnas In Erythropoiesismentioning
confidence: 96%
“…There is a high expression of miR-126 in hematopoietic precursors, while the expression of it is reduced in the process of differentiation into erythroid cells in vivo (Byon and Papayannopoulou, 2012). In addition to PTPN9, expression suppression of other downstream target (s) by miR-126 may be involved in erythropoiesis inhibition, and further studies are needed to identify them (Huang et al, 2011;Byon and Papayannopoulou, 2012). miR-191: During the development of RBCs, nuclear chromatin is fully compressed until the reticulocytes lose their nucleus.…”
Section: Role Of Mirnas In Erythropoiesismentioning
confidence: 99%
See 2 more Smart Citations